Experimental Analysis of Friction Stir Welding of Dissimilar Alloys AA6061 and Mg AZ31 Using Circular Butt Joint Geometry. (2016) - Sharma, Heena K.; Bhatt, Kamlesh; Shah, Krunal; Joshi, Unnati
Abstract: The Aluminium alloy 6061 and Magnesium alloy AZ31 plates of 6 mm thickness are welded in circular butt joint geometry by friction stir welding (FSW) process, using CNC vertical milling machine. Process parameters such as welding speed and tool rotational speed play an important role to obtain a better weld joint for dissimilar metals/materials. The friction stir welding tool is one of the critical components to the success of this process. It consists of a cylindrical shoulder and a pin with different geometry. In the experimental work, the said tool has been designed with cylindrical pin having four different geometries for friction stir welding of the dissimilar circular metal plates. Friction stir welding has been carried out at welding speed varying from 10 to 40 mm/min and tool rotational speed from 800 to 2000 rpm. Effects of process parameters on butt welded circular joint were investigated for weld strength. In this research work, it is found that welded joint between dissimilar metals alloys Al 6061 and Mg AZ31 can be formed using friction stir welding by selecting proper tool pin profile and welding parameters. It is suggested that friction stir welding of Aluminium alloy and Magnesium alloy with circular butt joint geometry would be useful in the future for automobile applications by getting the benefits from each material in a functional way.